The Effectiveness of the umbrella cluster strategy in synthetic thinking for first-year intermediate students in chemistry - Ahmed Laibi Hussein Al-Tamimi, (Technium Social Sciences Journal, 2024)
The research showed the effectiveness of the (Umbrella cluster strategy) strategy and its impact on the synthetic thinking of first-year intermediate students in chemistry for the academic year (2023-2024). The research sample consisted of students from Future Leaders Secondary School for Outstanding Students The research group, affiliated with the General Directorate of Education of Baghdad, Al-Karkh III, and the two research groups were equally chronologically aged., intelligence, and grade. Previously for the science subject, The sample consisted of 56 students, with 28 students. for each grade. The synthetic thinking scale prepared by (Kazim, 2023) was relied upon, which consisted of (40) items. The results were discussed and suggestions and recommendations were presented by the researcher.